Genetic engineering strategies to enhance antitumor reactivity and reduce alloreactivity for allogeneic cell-based cancer therapy - Chen, Yuning; Zhu, Yichen; Kramer, Adam; Fang, Ying; Wilson, Matthew; Li, Yan-Ruide; Yang, Lili (Frontiers in Medicine, 2023)
The realm of cell-based immunotherapy holds untapped potential for the development of next-generation cancer treatment through genetic engineering of chimeric antigen receptor (CAR)-engineered T (CAR-T) cell therapies for targeted eradication of cancerous malignancies. Such allogeneic “off-the-shelf” cell products can be advantageously manufactured in large quantities, stored for extended periods, and easily distributed to treat an exponential number of cancer patients. At current, patient risk of graft-versus-host disease (GvHD) and host-versus-graft (HvG) allorejection severely restrict the development of allogeneic CAR-T cell products. To address these limitations, a variety of genetic engineering strategies have been implemented to enhance antitumor efficacy, reduce GvHD and HvG onset, and improve the overall safety profile of T-cell based immunotherapies. In this review, we summarize these genetic engineering strategies and discuss the challenges and prospects these approaches provide to expedite progression of translational and clinical studies for adoption of universal cell-based cancer immunotherapy.